Co-production in mental health care. Issue 4 (14th December 2015) - Clark, Michael
Abstract : Purpose: – Co-production is becoming a more widely used term in mental health care in England, but it is not always clear what this means nor what the evidence base is behind particular uses of the concept. The purpose of this paper is to set some of this discussion into a historical context and examine some of the relevant evidence base to begin to highlight the challenges with operationalising more co-production. This is by way of setting the scene for the other articles in this special edition of the journal. The paper then provides an overview of the other articles on co-production in this edition. Design/methodology/approach: – The paper is a short review and discussion of some key issues and evidence relevant to co-production in mental health. Findings: – Some key historical insights from other moves to transform mental health care are discussed, recognising that these developments can take a long time to reach maturity in services and practice across the whole country. The discussion of some pertinent research and of the other articles in this special edition helps to highlight what foundations the author have in place for greater co-production in mental health care, and what remains as some of the challenges and gaps in the knowledge. Originality/value: – The paper provides a historical overview of some key issues, evidence and lessons pertaining to moves to develop more co-production in mental health.